Assessing the magnetic flux leakage contraction parameters for the fatigue life prediction of SAE1045 steel specimens. (December 2021) - Sahadan, Siti Norbaya; Abdullah, Shahrum; Arifin, Azli; Singh, Salvinder Singh Karam
Graphical abstract: Abstract: The aim of this paper is to assess the stress concentration zone (SCZ) of a circular smooth specimen at an early stage. Following the detection of the stress concentration zone, the specimen residual life was calculated and compared to the experimental result. Uniaxial loading on the servo-hydraulic testing machine was used for the laboratory testing. The stress concentration tester was used to detect the SCZ on the specimen, based on spontaneous surface micro magnetic signals on the ferromagnetic surface. In addition, cyclic testing for fatigue characteristics was conducted at 70% and 75% of ultimate tensile stress (UTS). The results indicated that the estimated residual life for the 70% UTS was nearly identical to the experimental value, based on two magnetic parameters, i.e, Kmax and the contraction value. Meanwhile, the estimated residual life for the 75% UTS was equivalent to the experimental findings. The minimum and maximum error values for life estimation using both parameters were 0.47% and 24.35%, respectively, for the contraction value. The correlation value, R 2, between the estimated life using MMM and experimental life was 0.95, showing good estimation. All the estimated life data using this method was distributed within the range of a 95% to 90% confidence interval. Hence, the proposed method can be used to predict the fatigue life of ferromagnetic components through magnetic flux leakage signals, especially in the stress concentration region.